Molecular Identification of Fire Worms in Indonesian Intertidal Waters: The First COI Gene-Based DNA Barcode of Eurythoe complanata - Rosyada, Vivian; Buhari, Nurliah; Jefri, Edwin (Jurnal Kelautan Tropis, 2025)
Polychaetes, including fireworms, play crucial ecological roles such as nutrient recycling and forming a vital part of the marine food web. However, their accurate identification is challenging due to morphological complexity and the presence of cryptic species. DNA barcoding, particularly targeting the cytochrome oxidase subunit I (COI) gene, has emerged as a powerful tool for species delineation due to its high accuracy and reproducibility. This study aims to molecularly identify fireworm specimens collected from Indonesian intertidal zones using COI gene barcoding. Fireworm samples were collected from Lombok waters, followed by DNA extraction, PCR amplification, electrophoresis, and DNA sequencing. The DNA data were analyzed using MEGA-X software to compare the sequences with those in the database and identify the species. A phylogenetic tree was constructed to illustrate the relationships between the analyzed species. The results show that the fireworm sample from Lombok is classified as Eurythoe complanata, a member of the Amphinomidae family. COI genetic analysis revealed a 658 bp DNA fragment with 77.19% similarity to the same species from India. The phylogenetic tree indicated a close relationship with the Indian species, supported by a bootstrap value of 85. Genetic distances ranged from 0.02 to 0.48, and the dominance of A+T nucleotides suggests the presence of genetic variation.